Intravenous amisulpride for the prevention of postoperative nausea and vomiting: two concurrent, randomized, double-blind, placebo-controlled trials - Gan, Tong-Joo; Motsch, Johann (Anesthesiology, 2017)
Two Concurrent, Randomized, Double-blind, Placebo-controlled Trials
Gesehen am 15.06.2018
Accepted for publication October 11, 2016